1999
DOI: 10.1175/1520-0469(1999)056<1308:moteog>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the Effects of Gravity Waves in the Middle Atmosphere Using Parametric Models of Density Fluctuations. Part I: Vertical Wavenumber and Temporal Spectra

Abstract: Parametric models of spectral analysis offer several distinct advantages over statistical methods such as the correlogram analysis. These advantages include higher spectral resolution and the ability, in principle, to separate correlated (i.e., wave) behavior from noise-driven (i.e., turbulent) behavior in the measurements. Here parametric models are used to highlight the spatial and temporal intermittency of the gravity wave spectrum. In Part II of this series the spatial and temporal spectrum are used to cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Hence, we discuss the extraction of gravity waves from temperature data rather than atmospheric density, although most of the results can be applied to density measurements as well. For different methods of extracting gravity waves from density measurements see, e.g., Sica and Russell (1999), Thurairajah et al (2010) and Mzé et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, we discuss the extraction of gravity waves from temperature data rather than atmospheric density, although most of the results can be applied to density measurements as well. For different methods of extracting gravity waves from density measurements see, e.g., Sica and Russell (1999), Thurairajah et al (2010) and Mzé et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…Similar filters are used in space or time for spectral analysis of atmospheric waves (e.g., Sica and Russell, 1999). Filter parameters are reported in the data files that are locally produced and distributed to the scientific user community.…”
Section: Review Of Vertical Resolution Definitions Used By Ndacc Lidamentioning
confidence: 99%
“…The analysis of high resolution radiosonde measurements by Vincent et al [1997] has suggested that the gravity wave field in the lower stratosphere may actually be composed of a mixture of quasi-monochromatic gravity waves and a broad spectrum. Sica and Russell [ 1999] have also shown that intermittent features with narrow bandwidths often tend to dominate the upper straWspheric m spectrum, although a smooth rn'3-type power law exists if sufficient averaging (e.g. hours) is performed.…”
Section: The Problemmentioning
confidence: 99%